Inter- and intra-observer variability for the assessment of coronary artery tree description and lesion EvaluaTion (CatLet©) angiographic scoring system in patients with acute myocardial infarction. Issue 4 (20th February 2021) - Liu, Jin-Mei; He, Yang; Teng, Ruo-Ling; Qian, Xiao-Dong; Dai, Yun-Lang; Xu, Jian-Ping; Zhao, Xin; Jiang, Ting-Bo; He, Yong-Ming
Abstract: Background: Previously, we developed a novel C oronary A rtery T ree description and L esion E valuaT ion (CatLet © ) angiographic scoring system, which was capable of accounting for the variability in the coronary anatomy and assisting in the risk-stratification of patients with acute myocardial infarction (AMI). Our preliminary study revealed that the CatLet score better predicted clinical outcomes for AMI patients than the Synergy between Percutaneous Coronary Intervention with Taxus and Cardiac Surgery score. However, the reproducibility of the CatLet score in both inter- and intra-observer remains to be evaluated. Methods: A total of 30 consecutive AMI patients, admitted in September of 2015, were independently assessed by two experienced interventional cardiologists to evaluate the inter-observer reproducibility of the CatLet score. Another set of 49 consecutive AMI patients, admitted between September and October in 2014, were assessed by one of the two interventional cardiologists on two occasions 3 months apart to evaluate the intra-observer reproducibility of the CatLet score. The weighted kappa was used to express the degree of agreement. Results: The weighted kappa values (95% confidence interval) for the intra- and inter-observer reproducibility of the CatLet Score were 0.82 (0.59–1.00, Z  = 7.23, P  < 0.001) and 0.86 (0.54–1.00, Z  = 5.20, P  < 0.001), respectively, according to the tertile analysis (≤14, 15–22, >22). Regarding the adverse characteristics pertinent to lesions and dominance parameters, the kappa values for the inter-observer variability were 0.80 (0.56–1.00, Z  = 6.47, P  < 0.001) for total number of lesions, 0.57 (0.28–0.85, Z  = 3.03, P  < 0.001) for bifurcation, 0.69 (0.43–0.96, Z  = 5.06, P  < 0.001) for heavy calcification, 1.00 (0.72–1.00, Z  = 6.93, P  < 0.001) for tortuosity, 0.54 (0.26–0.82, Z  = 3.78, P  < 0.001) for thrombus, 0.69 (0.48–0.91, Z  = 6.29, P  < 0.001) for right coronary artery dominance, 0.69 (0.41–0.96, Z  = 4.91, P  < 0.001) for left anterior descending artery length, and 0.22 (0.06–0.51, Z  = 1.56, P  = 0.06) for diagonal size. Equivalent values for the intra-observer variability were moderate to almost perfect (range 0.54–1.00). Conclusions: The reproducibility of the CatLet angiographic scoring system for evaluation of the coronary angiograms ranged from substantial to excellent. The high reproducibility of the CatLet angiographic scoring system will boost its clinical application to patients with AMI.